Intricate interplay between astrocytes and motor neurons in ALS - Phatnani, Hemali P.; Guarnieri, Paolo; Friedman, Brad A.; Carrasco, Monica A.; Muratet, Michael; O’Keeffe, Sean; Nwakeze, Chiamaka; Pauli-Behn, Florencia; Newberry, Kimberly M.; Meadows, Sarah K.; Tapia, Juan Carlos; Myers, Richard M.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
ALS results from the selective and progressive degeneration of motor neurons. Although the underlying disease mechanisms remain unknown, glial cells have been implicated in ALS disease progression. Here, we examine the effects of glial cell/motor neuron interactions on gene expression using the hSOD1 ᴳ⁹³ᴬ (the G93A allele of the human superoxide dismutase gene) mouse model of ALS. We detect striking cell autonomous and nonautonomous changes in gene expression in cocultured motor neurons and glia, revealing that the two cell types profoundly affect each other. In addition, we found a remarkable concordance between the cell culture data and expression profiles of whole spinal cords and acutely isolated spinal cord cells during disease progression in the G93A mouse model, providing validation of the cell culture approach. Bioinformatics analyses identified changes in the expression of specific genes and signaling pathways that may contribute to motor neuron degeneration in ALS, among which are TGF-β signaling pathways.